Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.35808/ersj/1168
|View full text |Cite
|
Sign up to set email alerts
|

«Green Economy»: Emerging National Models, Estimations, Trends in EU and CIS

Abstract: Green economy as a transitional phase to sustainable development has gained impetus after adoption of the 2030 sustainable development goals. The article contains analysis of the existing conceptual foundations of the green growth together with the assessment tools thereof on the one part and the results of the green economy models under gradual formation in the EU and the CIS on the other part. Such approach allowed the authors to set forth the most urgent lines of development of the statistical assessment to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…Gissin, Mekhanrseva, Putilina and Surzhikov [42] state that, according to expert estimations, a green economy is capable of rapidly ensuring GDP growth and increasing income per capita and employment. In order to start the transition to a green economy, the authors have found that 2% of the global GDP in the period 2012-2050 should be invested in agriculture, housing and municipal services, electrical energy economics, fishing, forestry, production, industry, tourism, transportation, waste disposal and recycling, and water resource management [42].…”
Section: Diyar 2014mentioning
confidence: 99%
“…Gissin, Mekhanrseva, Putilina and Surzhikov [42] state that, according to expert estimations, a green economy is capable of rapidly ensuring GDP growth and increasing income per capita and employment. In order to start the transition to a green economy, the authors have found that 2% of the global GDP in the period 2012-2050 should be invested in agriculture, housing and municipal services, electrical energy economics, fishing, forestry, production, industry, tourism, transportation, waste disposal and recycling, and water resource management [42].…”
Section: Diyar 2014mentioning
confidence: 99%